The Health Effects of Cannabis and Cannabinoids: The Current State of Evidence and Recommendations for Research - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Significant changes have taken place in the policy landscape surrounding cannabis legalization, production, and use. During the past 20 years, 25 states and the District of Columbia have legalized cannabis and\/or cannabidiol (a component of cannabis) for medical conditions or retail sales at the state level and 4 states have legalized both the medical and recreational use of cannabis. These landmark changes in policy have impacted cannabis use patterns and perceived levels of risk. However, despite this changing landscape, evidence regarding the short- and long-term health effects of cannabis use remains elusive. While a myriad of studies have examined cannabis use in all its various forms, often these research conclusions are not appropriately synthesized, translated for, or communicated to policy makers, health care providers, state health officials, or other stakeholders who have been charged with influencing and enacting policies, procedures, and laws related to cannabis use. Unlike other controlled substances such as alcohol or tobacco, no accepted standards for safe use or appropriate dose are available to help guide individuals as they make choices regarding the issues of if, when, where, and how to use cannabis safely and, in regard to therapeutic uses, effectively. Shifting public sentiment, conflicting and impeded scientific research, and legislative battles have fueled the debate about what, if any, harms or benefits can be attributed to the use of cannabis or its derivatives, and this lack of aggregated knowledge has broad public health implications. The Health Effects of Cannabis and Cannabinoids provides a comprehensive review of scientific evidence related to the health effects and potential therapeutic benefits of cannabis. This report provides a research agenda2014outlining gaps in current knowledge and opportunities for providing additional insight into these issues2014that summarizes and prioritizes pressing research needs.

Pain Management for People with Serious Illness in the Context of the Opioid Use Disorder Epidemic: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The United States is facing an opioid use disorder epidemic with opioid overdoses killing 47,000 people in the U.S. in 2017. The past three decades have witnessed a significant increase in the prescribing of opioids for pain, based on the belief that patients were being undertreated for their pain, coupled with a widespread misunderstanding of the addictive properties of opioids. This increase in prescribing of opioids also saw a parallel increase in addiction and overdose. In an effort to address this ongoing epidemic of opioid misuse, policy and regulatory changes have been enacted that have served to limit the availability of prescription opioids for pain management. Overlooked amid the intense focus on efforts to end the opioid use disorder epidemic is the perspective of clinicians who are experiencing a significant amount of daily tension as opioid regulations and restrictions have limited their ability to treat the pain of their patients facing serious illness. Increased public and clinician scrutiny of opioid use has resulted in patients with serious illness facing stigma and other challenges when filling prescriptions for their pain medications or obtaining the prescription in the first place. Thus clinicians, patients, and their families are caught between the responses to the opioid use disorder epidemic and the need to manage pain related to serious illness. The National Academies of Sciences, Engineering, and Medicine sponsored a workshop on November 29, 2018, to examine these unintended consequences of the responses to the opioid use disorder epidemic for patients, families, communities, and clinicians, and to consider potential policy opportunities to address them. This publication summarizes the presentations and discussions from the workshop.

Medications for Opioid Use Disorder Save Lives - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
The opioid crisis in the United States has come about because of excessive use of these drugs for both legal and illicit purposes and unprecedented levels of consequent opioid use disorder (OUD). More than 2 million people in the United States are estimated to have OUD, which is caused by prolonged use of prescription opioids, heroin, or other illicit opioids. OUD is a life-threatening condition associated with a 20-fold greater risk of early death due to overdose, infectious diseases, trauma, and suicide. Mortality related to OUD continues to escalate as this public health crisis gathers momentum across the country, with opioid overdoses killing more than 47,000 people in 2017 in the United States. Efforts to date have made no real headway in stemming this crisis, in large part because tools that already exist2014like evidence-based medications2014are not being deployed to maximum impact. To support the dissemination of accurate patient-focused information about treatments for addiction, and to help provide scientific solutions to the current opioid crisis, this report studies the evidence base on medication assisted treatment (MAT) for OUD. It examines available evidence on the range of parameters and circumstances in which MAT can be effectively delivered and identifies additional research needed.

Measuring Recovery from Substance Use or Mental Disorders: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
In February 2016, the National Academies of Sciences, Engineering, and Medicine held a workshop to explore options for expanding the Substance Abuse and Mental Health Services Administration2019s (SAMHSA) behavioral health data collections to include measures of recovery from substance use and mental disorder. Participants discussed options for collecting data and producing estimates of recovery from substance use and mental disorders, including available measures and associated possible data collection mechanisms. This publication summarizes the presentations and discussions from the workshop.

Pain Management and the Opioid Epidemic: Balancing Societal and Individual Benefits and Risks of Prescription Opioid Use - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Drug overdose, driven largely by overdose related to the use of opioids, is now the leading cause of unintentional injury death in the United States. The ongoing opioid crisis lies at the intersection of two public health challenges: reducing the burden of suffering from pain and containing the rising toll of the harms that can arise from the use of opioid medications. Chronic pain and opioid use disorder both represent complex human conditions affecting millions of Americans and causing untold disability and loss of function. In the context of the growing opioid problem, the U.S. Food and Drug Administration (FDA) launched an Opioids Action Plan in early 2016. As part of this plan, the FDA asked the National Academies of Sciences, Engineering, and Medicine to convene a committee to update the state of the science on pain research, care, and education and to identify actions the FDA and others can take to respond to the opioid epidemic, with a particular focus on informing FDA's development of a formal method for incorporating individual and societal considerations into its risk-benefit framework for opioid approval and monitoring.

The Role of Nonpharmacological Approaches to Pain Management: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
Pain is a leading cause of disability globally. The dramatic increase in opioid prescriptions within the past decade in the United States has contributed to the opioid epidemic the country currently faces, magnifying the need for longer term solutions to treat pain. The substantial burden of pain and the ongoing opioid crisis have attracted increased attention in medical and public policy communities, resulting in a revolution in thinking about how pain is managed. This new thinking acknowledges the complexity and biopsychosocial nature of the pain experience and the need for multifaceted pain management approaches with both pharmacological and nonpharmacological therapies. The magnitude and urgency of the twin problems of chronic pain and opioid addiction, combined with the changing landscape of pain management, prompted the National Academies of Sciences, Engineering, and Medicine to convene a workshop on December 420135, 2018, in Washington, DC. The workshop brought together a diverse group of stakeholders to discuss the current status of nonpharmacological approaches to pain management, gaps, and future directions. This publication summarizes the presentations and discussions from the workshop.

Substance Use Disorders in the U.S. Armed Forces - Institute of Medicine (The National Academies Press, 2013)
Problems stemming from the misuse and abuse of alcohol and other drugs are by no means a new phenomenon, although the face of the issues has changed in recent years. National trends indicate substantial increases in the abuse of prescription medications. These increases are particularly prominent within the military, a population that also continues to experience long-standing issues with alcohol abuse. The problem of substance abuse within the military has come under new scrutiny in the context of the two concurrent wars in which the United States has been engaged during the past decade2014in Afghanistan (Operation Enduring Freedom) and Iraq (Operation Iraqi Freedom and Operation New Dawn). Increasing rates of alcohol and other drug misuse adversely affect military readiness, family readiness, and safety, thereby posing a significant public health problem for the Department of Defense (DoD). To better understand this problem, DoD requested that the Institute of Medicine (IOM) assess the adequacy of current protocols in place across DoD and the different branches of the military pertaining to the prevention, screening, diagnosis, and treatment of substance use disorders (SUDs). Substance Use Disorders in the U.S. Armed Forces reviews the IOM's task of assessing access to SUD care for service members, members of the National Guard and Reserves, and military dependents, as well as the education and credentialing of SUD care providers, and offers specific recommendations to DoD on where and how improvements in these areas could be made.